(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2017)
This article examines the normative approach to comparative religion in the Quran. The current conceptual study applies both inductive and deductive methods in analysing statements in the Quran and views by scholars. Beginning with the definition of normative comparison method, the current discussion goes on to analyse its application in the Quran. The analysis suggests that the method of normative comparison of religion should be divided into two, namely the prudential normative comparison method and the offensive normative comparison method. Also importantly, the current study found that the Quran restrains from applying the offensive normative comparison method and focuses instead on the prudential normative comparison method. Makalah ini mengkaji pendekatan normatif dalam perbandingan agama yang diaplikasikan dalam kitab suci al-Quran al-Karim. Makalah ini merupakan kajian konseptual berasaskan metode induktif dan deduktif terhadap penyataan-penyataan al-Quran dan pandangan para sarjana. Bertitik tolak daripada definisi Metode Perbandingan Normatif, kajian ini menganalisis aplikasi metode ini dalam al-Quran. Dapatan analisis menunjukkan bahawa Metode Perbandingan Normatif terhadap agama yang dikemukakan dalam al-Quran perlu dipecahkan kepada dua bahagian, iaitu Metode Perbandingan Normatif Berhemah dan Metode Perbandingan Normatif Ofensif. Dalam melakukan perbandingan, al-Quran tidak menggunakan Metode Perbandingan Normatif Ofensif, sebaliknya tertumpu kepada Metode Perbandingan Normatif Berhemah.